Pro LINQ Object Relational Mapping with C# 2008 - Mehta, Vijay P. (Springer, 2017)
It is nearly impossible today to write enterprise software without the use of one or more relational databases. Granted, there are cases when the data is transient and not stored in a database, but for the most part, software needs to consume and manipulate data in a database. It sounds easy, but there are hundreds of ways to connect software systems to databases and thousands of people who think they have the skeleton key for data access layers. Pro LINQ Object Relational Mapping in C# 2008 explains an efficient, repeatable way to apply industry design patterns to build scalable object–oriented data access layers.